KREASI BURUNG BEO NIAS SEBAGAI MOTIF KEMEJA BATIK - Anisa Giantari; Dini Yanuarmi; Taufik Akbar; Wirma Surya (Style : Journal of Fashion Design, 2022)
The Nias parrot is an endangered species native to Nias, North Sumatra. The body of the Nias parrot is black, a little white on the wings, earlobes and legs are yellow. The distinctive features of the Nias parrot with other parrots are its larger body size and united earlobes. The concept of the creation of the Nias parrot is taken from the life of this animal, in the form of freedom to fly in nature because many Nias parrots are caught, this concept also tells about the activity of tree branches. The production process of this work uses a theoretical basis that includes form, function, motif, creation and colour. The process of producing this work goes through three stages which are the exploration stage which is finding sources of ideas through library sources or interviews, designing which is pouring ideas into alternative sketches which then become the chosen design, the embodiment stage which is the process. the embodiment of the work that has been designed, the technique used is the batik technique, with silk cotton fabric and using reactive dyes, after the batik process is completed, the material is sewn into men's clothes.